1997
DOI: 10.1089/dna.1997.16.769
|View full text |Cite
|
Sign up to set email alerts
|

Closely Related Genes Encode Developmental and Tissue Isoforms of Porcine Cytochrome P450 Aromatase

Abstract: We examined the chromosomal basis for the synthesis of tissue (ovary, endometrium/placenta, and peri-implantation blastocyst) isoforms of cytochrome P450 aromatase in the pig. DNA fragments derived from three distinct porcine aromatase chromosomal genes were cloned and characterized. The porcine type III aromatase gene encoding the blastocyst aromatase isoform was found to consist of nine coding exons and two mutually exclusive, 5' untranslated exons (designated E1A and E1B), collectively spanning 30 kb or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Results of studies using RACE (rapid amplification of cDNA ends) cDNA libraries made from cattle, horse, and pig placental tissues have indicated that tissue-specific promoters upstream of placenta-specific exons also regulate placental expression of the CYP19 gene in these species (25). In those species in which the 5Ј flanking regions of the CYP19 placenta-specific promoters have been cloned, there is low sequence identity among species (25,26). Furthermore, in the human CYP19 gene, the placenta-specific promoter lies Ϸ40 kb upstream of the start site of translation, whereas in the bovine CYP19 gene, the placenta-specific promoter lies Ϸ19 kb upstream of the translation start site (27).…”
Section: Fig 2 Expression Of the Cyp19(i1)ϫ2400mentioning
confidence: 99%
See 1 more Smart Citation
“…Results of studies using RACE (rapid amplification of cDNA ends) cDNA libraries made from cattle, horse, and pig placental tissues have indicated that tissue-specific promoters upstream of placenta-specific exons also regulate placental expression of the CYP19 gene in these species (25). In those species in which the 5Ј flanking regions of the CYP19 placenta-specific promoters have been cloned, there is low sequence identity among species (25,26). Furthermore, in the human CYP19 gene, the placenta-specific promoter lies Ϸ40 kb upstream of the start site of translation, whereas in the bovine CYP19 gene, the placenta-specific promoter lies Ϸ19 kb upstream of the translation start site (27).…”
Section: Fig 2 Expression Of the Cyp19(i1)ϫ2400mentioning
confidence: 99%
“…Furthermore, in the human CYP19 gene, the placenta-specific promoter lies Ϸ40 kb upstream of the start site of translation, whereas in the bovine CYP19 gene, the placenta-specific promoter lies Ϸ19 kb upstream of the translation start site (27). In the pig, there is even greater complexity, because there may be as many as three CYP19 genes encoding tissue-specific isoforms with multiple promoter usage for some of the isoforms (26,28). Because of this complexity, it is not possible to begin to define the genetic basis for placenta-specific expression of human aromatase by comparison of promoter sequences.…”
Section: Fig 2 Expression Of the Cyp19(i1)ϫ2400mentioning
confidence: 99%
“…In mammals, with the exception of pig (Choi et al 1997, Graddy et al 2000, CYP19 is encoded by a single copy of the CYP19 gene, and the tissuespecific expression was achieved by the use of tissue-specific promoters and alternative splicing of 5 0 untranslated exons (Simpson 2003). However, two distinct CYP19 genes, namely cyp19a1a and cyp19a1b, which were expressed mainly in the ovary and brain respectively, were identified in teleosts, such as Carassius auratus (Tchoudakova & Callard 1998), Oncorhynchus mykiss (Tanaka et al 1992, Valle et al 2002, Danio rerio (Kishida & Callard 2001), Oreochromis niloticus (Kwon et al 2001), Dicentrarchus labrax (Blázquez & Piferrer 2004), Halichoeres tenuispinis (Choi et al 2005), Fundulus heteroclitus (Greytak et al 2005), and Epinephelus coioides (Zhang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Placental expression of P450AROM has also been documented in cows (9,10), pigs (11)(12)(13), and horses (9). A single CYP19 gene spanning more that 75 kb and containing nine coding exons (exons II-X) has been identified in humans (5,14,15), but there is evidence for multiple distinct, but closely related, aromatase genes in pigs (13,16,17).…”
mentioning
confidence: 99%